Nuclear transport receptor goes moonlighting - Gruss, Oliver (Nature cell biology, 2010)
The importin-β-like transport receptors and RanGTP govern selective transport of proteins into the nucleus. It has now been shown that importin-β2 (alternatively called transportin1) also selectively targets the motor protein Kif17 to primary cilia. In analogy to the nucleus, RanGTP in the intraciliary compartment mediates dissociation of Kif17 from its transport receptor and thereby completes import.
Gesehen am 01.06.2023